IMPLEMENTING INTERACTIVE READING MODEL TO TEACH HORTATORY EXPOSITION TEXT TOTHE ELEVENTH GRADERS OF SMAN 1 SOOKO MOJOKERTO (RETAIN, 2014)
IMPLEMENTING INTERACTIVE READING MODEL TO TEACH HORTATORY EXPOSITION TEXT TO THE ELEVENTH GRADERS OF SMAN 1 SOOKO MOJOKERTO Arista Nurhayati English Department, Languages and Arts Faculty, State University of Surabaya, noorhayati16@yahoo.co.id Aswandi, Drs., M. Pd. English Department, Languages and Arts Faculty, State University of Surabaya, aswandi20@yahoo.com Abstrak Penelitian ini merupakan sebuah penelitian deskriptif kualitatif yang menggambarkan bagaimana guru menggunakan model membaca interaktif dalam pengajaran teks hortatory exposition pada siswa kelas XI di SMAN 1 Sooko Mojokerto dan bagaimana respon siswa pada saat mereka diajarkan membaca teks hortatory exposition menggunakan model membaca interaktif. Penelitian ini dilaksanakan di kelas XI IPA 6 di SMAN 1 Sooko Mojokerto pada semester kedua. Data penelitian diperoleh dari observasi kelas, kuesioner siswa, dan wawancara dengan guru yang bersangkutan. Kemudian, data tersebut dianalisis menggunakan tiga langkah, yaitu data reduksi, penyajian data, dan verifikasi. Hasil analisis menunjukkan bahwa guru menggunakan model membaca interaktif dalam pengajaran teks hortatory exposition dengan langkah-langkah berikut: mengenalkan judul, membekali siswa dengan struktur bahasa dan pengetahuan linguistic terkait, berkonsentrasi pada pelafalan dan pengenalan kata, mengajak siswa memprediksi arti kata baru nenggunakan kamus dan konteks, meminta siswa mentransfer informasi tersurat dan tersirat ke dalam bentuk tabel, bertanya pada siswa tentang opini dan perasaan mereka mengenai isi teks, dan melaksanakan latihan tambahan. Sedangkan respon siswa pada saat mereka diajarkan teks hortatory exposition dengan menggunakan model membaca interaktif menunjukkan hasil yang bagus dari sisi pengembangan kosakata, latihan pelafalan kata, dan kesempatan untuk berkomunikasi. Berdasarkan hasil penelitian, guru disarankan untuk memakai teks yang memenuhi kriteria kesesuaian isi dengan topic bahasan, mudah untuk dieksplorasi, dan layak sebagai bahan bacaan. Di samping itu, peneliti selanjutnya harus fokus pada penggunaan model membaca interakrif untuk mengajarkan genre teks yang berbeda dan pada level siswa yang berbeda pula. Kata Kunci: model membaca interaktif, teks hortatory exposition, respon siswa Abstract This study is a descriptive qualitative research which describes how the teacher implements interactive reading model to teach hortatory exposition text to the eleventh graders of SMAN 1 Sooko Mojokerto and how are the students’ responses when they are taught reading hortatory exposition text by using that model. This study was conducted on the second semester of XI science 6 in SMAN 1 Sooko Mojokerto. The data was collected from classroom observations, students’ questonnaires, and an interview with the teacher. Later, the data were analized in three steps: data reduction, data display, and verification. The result showed that the teacher implemented the interactive reading model to teach hortatory exposition in these steps: introducing the title/headline; preparing the students’ structure and linguistic feature; focusing on the students’ pronunciation and word recognition; asking the students to find out unknown words by using context and dictionary; requiring the students to transfer the message from the text into a table; asking the students’ opinion and feeling toward the text; and conducting follow-up activities. Meanwhile, the students’ responses toward the implementation of interactive reading model were good in terms of vocabulary improvement, pronunciation practice, and opportunity for communication. Based on the result of this study, the researcher suggests to the teacher to use the text which fulfils the criteria of suitability of content, exploitability, and readability. Besides, the next researchers should be concern to use the interactive reading model to teach the different kinds of text and the other levels of the student. Keywords: interactive reading model, hortatory exposition text, students’ responses INTRODUCTION Reading is the source of meaningful and comprehensible linguistic input that helps unconscious language acquisition. Anderson (2003:68) states that reading is a process of combining information from a text and the reader’s background knowledge to get meaning. In addition, Krashen (1981) in Lyutaya (2011:27) argues that effective reading skills are essential in the English as Foreign Language situation because of limited exposure to spoken English. Therefore, reading becomes one alternative which encourages students with more language exposure to written English. However, there are many reasons why getting students to read English texts is an important part of teacher’s job. Firstly, it is simply because students want to be able to read texts in English for some purposes, such as for careers, study purposes, or simply for entertainment. Besides, Harmer (1998:68) believes that reading texts also provide good models for English writing and opportunities to study language components such as vocabulary, grammar, punctuation, etc. Secondly, it is the objective of the Indonesian curriculum that students are expected to be able to communicate in English, in which “to communicate” means “to produce spoken and written English texts”. Thus, anything that teachers can do to help them speak and write English texts easily must be a good idea. Furthermore, the approach adopted by the Indonesian curriculum is literacy approach. This approach defines reading and writing to achieve social purposes in context of use. Therefore, the teaching of English to senior high school students addresses informative text in contexts of use on some kinds of texts, such as discussion and exposition. An exposition text is a kind of factual text that should be mastered by the eleventh graders of senior high school as they come in contact with maps, menus, guides, brochures, newspapers, magazines, and the internet in the daily life. Exposition texts being taught at school are divided into two: hortatory exposition and analytical exposition. In this occasion, the writer concerns only at the teaching of hortatory exposition. According to Street (2002:34), students often come to high school with limited experience with content area texts on the textbook such as exposition and explanation. Further, the writer discovers that students have been engaged in reading a narrative text. They are excited in reading an adolescent novel, connecting their prior knowledge to the new one, and clarifying misconceptions. But they do not know the strategic reading skills to learn more about their textbook. They become passive, with simply skimming over the foreign words and pictures, making no real connections between the exposition text and their own experience. To make students engaged in reading an exposition text, teachers need to step in and offer support for them. In this case, the teacher can use interactive reading model to teach reading hortatory exposition. Interactive reading is another type of reading model which combines the elements of both bottom-up and top-down models. Furthermore, Stanovich in Nunan (1998:67) claims that interactive reading model is superior because it deals with the lack of the other models, and allows for the deficiencies at one level to be exchanged for at another. This model also suggests that a reader processes a text by using information from several different sources in the same time. These sources can be phonological, lexical, syntactic, semantic, and discourse knowledge. In short, interactive reading model is accepted as the most comprehensible description of reading process. As a matter of fact, interactive reading model is still rarely used in the teaching of reading. The teacher is usually focuses on exploring the grammatical structure and language features of the text without considering the student’s prior knowledge of the topic. Often, the teacher leads the reading discussion by reading the following questions first. Then, skimming or scanning the information to answer the questions and seeing dictionary to find vocabulary meaning. But later, the teacher does not relate the topic with the students’ experiences or arguments. Consequently, the students understand how to find out the information to answer the questions but often find difficulties in guessing word meaning from the context or the knowledge they already know. Therefore, the teacher needs to emphasize not only bottom-up but also top-down reading process to help students activate their background knowledge. Eventually, the students will be able to develop their thinking in higher level of comprehension. Finally, the interactive reading model is appropriate to be applied in teaching reading hortatory exposition. First, it is simply because a hortatory exposition text contains vocabulary with a particular content area, so that the terms are usually different with the vocabulary in a narrative. Second, it gives students an opportunity to explore vocabularies related to the content area and make connection between their prior knowledge and those vocabularies. In addition, Brown (2001:299) states that recent studies on teaching reading have shown that a combination of top-down and bottom-up or interactive reading model is an important part in successful teaching methodology because both processes are essential. Thus, this study is conducted to answer these following questions: (1) how is the implementation of interactive reading model to teach reading hortatory exposition to the eleventh graders of SMAN 1 Sooko Mojokerto? and (2) how are students’ responses when they are taught reading hortatory exposition by implementing interactive reading model?. Based on the problem questions, the aims of this study was to describe the implementation of interactive reading model to teach reading hortatory exposition to the eleventh graders of SMAN 1 Sooko Mojokerto and to know the students’ responses when they are taught reading hortatory exposition by implementing interactive reading model. Types of Reading According to Brown (2001:312), classroom reading performance is defined into two: oral and silent reading. Oral reading is the act of reading aloud. It is often used to develop pronunciation practice because the reader’s mistakes can be corrected by another reader at once. It also helps students to develop skills of speech and communication. On the other hand, silent reading is an individual activity in which communication is not between one reader and another, but between an author and a reader. Furthermore, silent reading in the classroom performance is divided into two: intensive and extensive reading. The main aim of intensive reading is developing students’ ability to decode message by drawing on syntactic and lexical cues and emphasizing skill for recognition. Moreover, Anderson (2003:71) adds that intensive reading includes a short text added by textbook activities to develop comprehension or particular reading skills in which the textbooks mostly use intensive reading approach. Therefore, the activities deal with the reading materials and the teacher’s guidance. On the other hand, extensive reading purposes to achieve general understanding of longer text such as book, essays, long articles, novels, etc. It can be an alternative to make reading more interesting and joyful. Lyutaya (2011:26) and Ono, et.al. (2004:12) agree that in extensive reading, students read for information and pleasure, with primary purpose of obtaining a general understanding of literary ideas, learn reading strategies, acquire new vocabulary, and increase their English proficiency as they read a large quantity of material both inside and outside of the classroom. Finally, it can be said that in intensive reading activities, students are in the main exposed to short texts which are used to give typical example of text genres, or to provide the method for targeted reading strategy practice. While the goal of extensive reading, on the other hand, is to enrich students reading ability with large quantities of targeted language input with few or possibly no specific tasks. In short, the combination of both reading strategies will be a helpful strategy in reading comprehension. Level of Reading Comprehension Reading comprehension is an active process that must be developed if a learner wants to be a proficient reader. Comprehension is understand what is being said or read and understand what someone reads can be viewed according to the level of thinking. According to Berry (2005:1-2), when reading, the reader’s level of thinking usually related to understanding at three kinds of information. They are literal level which involves what the author is actually saying, interpretive level which deals with what the author means by what is said, and applied level which concerns with why the author says what he or she says. These levels of comprehension are what make a reader skilled. With that thought in mind, it has been shown that strong readers make good writers. Furthermore, the integration of good level of reading comprehension and continued exposure to the English language enables readers to be writers which are better in expressing themselves. The Stages of Teaching Reading Abbott (1981:95) and Brown (1994) in Correia (2006:17) agree that there should be three stages to the teaching of reading. The first phase is pre-reading discussion, which involves introducing the topic and preparing students for the text (Papalia, 1987:75). In addition, Abbott (1981:95) describes pre-reading activities like asking the students to read only the headings or the title to anticipate content, showing a picture or video to recall students’ description about the text they are going to read, and explaining generic structure, language features, and some vocabularies as keywords which the meaning is needed to understand the text. The second phase includes while-reading tasks, in which students are provided with a set of instructions to give them a purpose for reading and to serve as a guide for them as they read. Abbott (1981:96) describes the activities which sharp the students’ cognitive just like identifying the main idea, finding details, following a sequence, inferring opinion, accepting the author’s purpose and opinion, and knowing the generic structure and language features. The third phase includes post-reading exercises, in which students are given short comprehension questions, vocabulary work, opportunity for discussion of the topic and the author’s reasoning, and/or a summary writing assignment. Reading Processes: bottom –up or top-down? One side consists of experts who claim that the process of reading begins with letters and their sounds (phonics). They support bottom-up model to explain the reading process. Additionally, Harmer (2007:270) describes that in bottom-up processing, the reader focuses on individual words, phrases, cohesive devices, and understands the text by combining those detail parts to make a complete understanding. In other side, other experts who subscribe top-down model of the reading process believe reading as mainly "externally guided". In addition, Goodman (1976), a top-down model supporter, in Anderson (2003:71) criticizes bottom-up model because the reader becomes “word callers” who can read words on the text but do not understand what they have read. Moreover, Goodman (1976) believes that by breaking whole text into little pieces of words, the teacher will make reading difficult. However, neither bottom-up nor top-down model of the reading process totally accounts for what occurs during the reading process. So, there should be an interactive model which is viewed as incorporation. The word “interactive” in this model refers to the interaction between bottom-up and top-down processing skills. Interactive model According to de Debat (2006:13), “the interactive model acknowledges that lower level processing skills are essential for fluent and accurate reading; it also emphasizes that as bottom-up processing becomes more automatic, higher-level skills will become more engaged”. In spite of the fact that the field of teaching of reading today is strongly influenced by top-down processing perspectives, efficient and effective reading involves both processes interacting simultaneously. Moreover, Anderson (2003:72) agrees that interactive model combines the elements of both bottom-up and top-down models. Stanovich (1980) and Murtagh (1989) in Anderson (2003:72) do stress that proficient readers are readers who can combine both bottom-up and top-down processes as a way to get information from many sources of knowledge. In short, interactive model is the most comprehensive description of reading process. In the classroom, an interactive model is the best description of what happens when the students read. For example, the bottom-up model is used when the students deal with the text component such as words, grammar, and the like. While the top-down model is used when the students predict difficult word’s meaning by using their background knowledge. Griffiths, et.al. (2010:6) argues that reading is an interactive and iterative process which represents either bottom-up or top-down. Therefore, to teach interactive reading, the teacher should promote interaction between individuals (the teacher and students) and the text. This interaction should involve both top-down and bottom-up reading and cognitive processes. The Interactive Approach Anderson (2003:72) argues that an interactive approach to reading includes aspects of both intensive and extensive reading. Applying this approach, the teacher needs to provide the students with a short text to teach specific reading skills and strategies clearly. Besides, the teacher needs to make them more likely to read longer texts without an emphasis on reading test. However, the teacher should be aware that the use of a textbook in the classroom will not meet the teaching reading of both intensive and extensive reading. Therefore, the teacher’s creativity in selecting reading supplement beyond textbook is also necessary. According to Nuttall (1996) in Brown (2001:314), there are three criteria for reading text selection: Suitability of content: material in which students will find interesting, enjoyable, challenging, and appropriate for their purposes in learning English; Exploitability: a text which facilitates the achievement of a particular language and content aims, that is exploitable for instructional assignments and techniques, and that is integratable with other skills Readability: a text with lexical and structural difficulty that will challenge students without forcing them. In addition, Papalia (1987:77) argues that when the teacher uses interactive approach in teaching reading, the students should be given the opportunity to relate their own lives, activities, and interests concerning to what is being read in the second language. To provide greater interaction between the text and the students, the teacher should stimulate work in groups, where the students have the opportunity to work together and learn from each other. However, small-group and pair work are considered suitable because both provide greater student-student interaction than large-group. The students who participate in a small group obtain knowledge not only from what they have read, but also through working with other students. Thus, through the checks and other’s contribution, they learn to relate the knowledge meaningfully and to develop new and richer interpretations of the text they read. The Principles of Teaching Reading According to Harmer (1998:70) there are some principles to teach reading. These six principles could be consideration for teacher to teach reading effectively. They are: ü Reading is not a passive skill ü Students need to be engaged with what they are reading ü Students should be encouraged to respond to the content of a reading text not just to the language. ü Prediction is a major factor in reading ü Match the task to the topic ü Good teacher exploit reading text to the full Taking into account those points, the use of interactive reading model is suitable with the teaching reading principles. Because interactive reading model provide opportunity for students to be active in reading process and recommend various methods for the teacher to engage students to read comprehensively. The Elements of Hortatory Exposition A hortatory exposition text is a type of written (or spoken) text which explains to the readers (or listeners) that an issue should or should not happen by presenting one side of an issue with one-side argument to persuade them. It contains facts, opinions, reasons, and ideas. The positive of negative arguments related to an issue are presented to persuade the readers. This text may be presented in scientific books, school textbooks, journals, magazines, articles on newspaper, academic speech, research report, and so on. Therefore, it is popular among academic community. According to Priyana (2008:132), the generic structure of hortatory exposition text are thesis as the general statement of topic discussed, arguments which are arranged according to the writer’s choice, and recommendation which contains what should or should not happen. The Interactive Reading Model in Teaching Reading Hortatory Exposition Text The following are some typical activities of interactive reading model which combine bottom-up and top-down processes during a reading section: Pre-reading: Informing the students about the topic of a text will be read (i.e. by asking the students to read only the headings or the title to anticipate content, showing a picture or video to recall students’ description about the text). Giving task to invite comparison between the culture of students’ native language and target language learned. Explaining generic structure, language features, and some key concepts which likely to encounter during reading. Inviting students’ participation. While reading: Focusing on students’ pronunciation or intonation. Identifying the main idea and explicit or implicit information in detail. Asking the students to infer their opinion toward the topic. Interrupting reading process to explain grammatical structure and to predict what happen next. Asking students to look for unknown word meaning on dictionary and to predict unknown word meaning from context. Requiring students to transfer information into a table or chart. Post-reading: Giving exercises in order to enhance comprehension (i.e. fill in blank, true/false or multiple choices). Giving tasks which require students to recognize grammatical units (i.e. verb inflections or derivations). Asking students to memorize new words and expressions and to state their own opinion toward the topic. Teaching students to use reading strategies. Conducting follow up activities (i.e. writing summary, topic discussion). RESEARCH METHODOLOGY The purpose of this study was to give description and interpretation about the implementation of interactive reading model to teach reading hortatory exposition text and the students’ responses toward the interactive reading model. Therefore, the writer used descriptive qualitative research which was designed to obtain information concerning in the implementation of interactive reading model to teach reading hortatory exposition texts. This design focused on understanding events through verbal narratives and observations, exploring not only what appeared during the observation but also the participant’s feeling and opinion. The study was conducted in SMAN 1 Sooko Mojokerto. The subject of this study was the English teacher and the 28 students of XI IPA 6. The subjects were selected purposively from the population of eight classes of eleventh graders in SMAN 1 Sooko Mojokerto. In this occasion, the students of XI IPA 6 were chosen because according to the teacher, they were less enthusiastic and had low motivation in learning English. Meanwhile, the main instrument in a qualitative study was the researcher itself because he or she was personally involved in the research. However, a researcher needed the other instruments to avoid observer bias. In this occasion, there were three instruments used to collect data: Observation checklist and field note According to Ary (2010:216), in qualitative research, observations are made in order to get a comprehensive picture of a situation and the product of the observations is notes or narratives. The observation checklist was adapted from Brown (2001:432-434). It presented a list of the behaviors that were to be observed as follows: Teacher’s behaviors; including preparation, presentation, teacher-students interaction, and personal characteristics. Teaching methods; including pre-, while-, and post-reading activities during the implementation of interactive reading model. Students’ behaviors; including students’ acts and responses during the implementation of interactive reading model. While field note was used to record anything the researcher found, saw, heard, and thought during the observation which was not written in the checklist. This was the blueprint of the observation checklist: Questionnaire Questionnaire was used to find out the students’ responses toward the implementation of interactive reading model to teach reading hortatory exposition texts. The questionnaire was contained of questions dealt with the students’ opinion toward English subject, the reading model used by teacher to teach reading, and the reading materials. Interview An interview was used to help understand the subjects’ experiences and the meaning they made of them. Ary (2010:438) adds that interviews may provide information that cannot be noted through observation, or they can be used to verify observation. For example, observing a teacher in a classroom told us something about the behavior, but interviewing helped us to put the behavior in context and helped us understand actions and choices. In this case, the researcher used unstructured interview which was a conversational type of interview in which the questions arise from the situation. It was conducted by the researcher to find out the teacher’s perspective about the implementation of interactive reading model in order to reflect on his or hers to avoid observer effect. Thus, the result would be used to answer the first research question regarding the implementation of interactive reading model to teach hortatory exposition text. Furthermore, the instruments were used to collect data about the participants’ experiences and perspectives. Firstly, the researcher observed the activities happened by doing two days classroom observation. During the observation, the researcher used non-participant observation in which the researcher did not directly involved in the activities but he or she sat on the back side and observed. Secondly, the researcher held an interview with the subject teacher to match perfectives. Finally, the researcher gave the students questionnaire to get information about their responses toward the implementation of the interactive reading model. The next step conducted after collecting data was data analysis. “Analysis involves reducing and organizing the data, synthesizing, searching for significant patterns, and discovering what is important” (Ary, 2010:481). The researcher must organize what he or she has seen, heard, and read and tried to make sense of it in order to create explanations, developed theories, or posed new questions. There were 3 steps conducted to analyze and interpret the data. They were: Data reduction Firstly, the researcher analyzed the activities conducted by the teacher and students when the interactive reading model was applied. She got more additional information from the field note such as the students’ scores from the post-reading activities. Then she made a transcript from the recording. Secondly, the researcher collected the students’ questionnaire and teacher’s interview. Then, she transformed the answers into essay to make it easier to understood. Data display The researcher organized the information transformed in the previous step into a draw conclusion. Firstly, the researcher synthesized the information and ordered them in several sections. Secondly, the researcher explained about how and why the relationships between phenomena existed by connecting the new knowledge with what is already known. Then, the researcher arranged the results chronologically. Verification The researcher wrote the draw conclusion as the project progresses. Finally, the final conclusion would be appeared when the data analysis was over. RESULT AND DISCUSSION The researcher arranged the result of the study separately based on the problem questions. The data collected from the interview were used to answer the first question regarding the implementation of interactive reading model to teach hortatory exposition text and the data from the questionnaire was used to answer the second question regarding the students’ responses towards the implementation of interactive reading model. While the data collected from classroom observation was used to answer both questions. The Implementation of Interactive Reading Model in Teaching Reading Hortatory Exposition Texts The researcher did the classroom observation twice, on May 23rd and 27th, 2013. The time that was allocated for each meeting was 2 x 45 minutes containing three stages; pre-activity, while-activity and post-activity. Both meetings were scheduled at afternoon time. In the pre-reading stage, at the first meeting, the teacher reviewed the previous lesson. She explained the elements of hortatory exposition text. She presented a power point slide containing two texts with the same topic. Then, she asked the students to determine which one is hortatory exposition text. Finally, she invited the students to identify its generic structure and language feature. The students could follow the explanation quietly and firm. Even some students raised their hands quickly to answer the teacher’s questions. While the activities in the second meeting were almost the same as in the first meeting. The difference was, in the second meeting, the teacher only explained briefly and did not take much time as the first meeting due to the limited time. And there was no question from the students. Those activities during the pre-reading stage were in line with Papalia (1987:75) who states that during the pre-reading, the situation which generates expectations that will be help the students to predict the content of the passage that will be read should be introduced. In addition, it was appropriate with one of pre-reading activities described by Abbott (1981:95); asking the students to read only the headings or the title to anticipate content. For instance, the teacher asked the students to read two different texts then determined which one was hortatory exposition text. She also explained the elements of hortatory exposition such as generic structure and language feature. Meanwhile, while-reading activities at the first meeting were started by the teacher by telling the lesson objective. Then, she played a three-minute clip entitled ‘Dove’ before delivered the material. The students watched the clip attentively. After that, she delivered questions related to the clip and asked them to predict the idea. Next, the teacher grouped the students and distributed the copy of material to each group. Before small group work started, there was a read-aloud session. In turn, the students raised their hands and the teacher pointed out one of them to read the text partly. She listened to the student’s reading attentively. She also gave direct correction when the student made pronunciation mistake. After that, they discussed the unknown words. On that occasion, the teacher chose to use the video entitled ‘Dove’ in order to relate the students background knowledge and the text entitled “Cosmetic Dangers: Is Make-up Killing You?”. The video showed a process in which an ordinary woman became very beautiful after wore a set of makeup. A professional photographer took her picture, edited it, then made the picture of her face became an icon of a famous beauty product. The teacher aimed to describe how cosmetics were popular among people without consideration of its danger. However, she asked the students whether they wear cosmetics, why they wear it, and whether they realize its danger or not. After that, she gave the text and discussed the unknown words with the students. She asked them to find out the word meaning by using context and their knowledge first before using dictionary. The teacher also contributed her opinion in order to build interaction between the teacher, the students, and the text. While the while- reading activities at the second meeting were almost the same with the first one. But, the teacher did not present any video. Firstly, she told the students that they would learn about another hortatory exposition text again. Secondly, she gave the reading material entitled “Fifty Shades of Nuclear Energy”. Next, she asked them to read it at glance in order to guess the main idea and unknown words. They used both context and dictionary to find out the word meaning. According to the researcher, the activity of showing video should be done in pre-reading stage. As Abbott (1981:95) explained that pre-reading activities includes asking the students to read only the title to anticipate content, showing a picture or video to recall students’ description, and explaining generic structure, language features, and some vocabularies. In addition, Daniels and Zemelman (2004:108) argued that the discussion of the video content is called “anticipation guide” which provides a structured forum for students to think carefully about a text’s concepts before they actually read the text. But, the teacher personally supposed that the video was used as an introduction to the coming text. It aimed to focus the reading process on purpose to clarify content. It has no connection with the texts used previously in the pre-reading stage. Thus, she put it in the while-reading stage. Another thing observed was the use of “leading questions” after showing the video. These questions were used to recall students’ existing knowledge. Moreover, Wahjudi (2010:3) agreed that “leading questions provide the students with the right direction to comprehend the text, so these questions should not ask for detailed answers”. In fact, when the teacher delivered the questions (i.e. whether the students wear cosmetics and whether they realize its danger or not), she waited for some time then repeated the questions with higher voice to get the students answer. Regarding to this, it would be better for the teacher to let the students keep their answer in mind. Then, in post-reading stage at each meeting, the teacher explained about what the students had to do with the assignments. Students worked in small groups at the first meeting whereas in the second meeting they worked individually. The students did the assignments seriously while the teacher walked around from one bench to another to monitor the students’ work. At the post-reading stage, students were supposed to apply what they possessed at pre- and while- reading stages. Furthermore, good post-reading activities should be able to get the students to recycle some aspects from their while-reading activities, to share opinions, ideas, feelings, and to give reasons to communicate. Therefore, the teacher made different assignments for each meeting. For the first meeting, the assignment was in the form of group discussion. Each group had to transfer the messages on the text into a table. They also required giving opinion about the writer’s point of view and the problem solution. Those assignments aimed to allow the students to respond to the text creatively. Additionally, the students’ assignment for the second meeting was making 100 words summary. As “reading comprehension should not be alienated from the other skills” (Harmer, 2007:267), the teacher chose summarizing activity to link reading and writing skills. Based on the class observation, the researcher concluded that the teacher did the activities according to her lesson plan in a good sequence. She implemented the interactive reading model mostly during the reading lesson. They are informing the students about the topic, preparing their structure and linguistic feature, focusing on the students’ pronunciation and word recognition, and conducting follow up activities. But, in some occasion, the teacher has different consideration with Abbott (1981) in positioning the activities of teaching stages. However, there were some missed activities such as giving assignment which require the students to memorize new words and expression and relate the students’ knowledge about their native and the target language. Furthermore, the teacher has a good personality and appearance. She was patient in eliciting the students’ response. She maintained eye contact with the students and talked some humors to avoid students’ anxiety. Her speaking was very fluent. She was relaxed in voice but she explained the material with clarity and intonation. Moreover, she was neat and tidy. The Students’ Responses When They Are Taught Reading Hortatory Exposition by Using Interactive Reading Model For the second research question, “How are students’ responses when they are taught reading hortatory exposition by implementing interactive reading model?”, the researcher gathered the data from observation checklist which deal with the students’ behaviors. Another data was gathered from the questionnaires deal with the students’ feeling and opinion during the observation. From the observation conducted, it could be said that the students’ response to the use of interactive reading model was good in terms of pronunciation or speaking practice. Based on the teaching and learning process, the students raised their hands enthusiastically to get chance in read-aloud session. Besides, the students asked and exchanged opinion in English during group discussion. Students’ own words were widely used in transferring the idea from text to a table and responding the questions. Then, the researcher concluded that the students’ response toward the use of small group discussion was good in terms of opportunity for communication. Based on the questionnaire, there were a couple of students who were not interested in the reading material because they felt less of vocabulary size. But in fact, the students could guess the meaning of difficult words by using dictionary and their background knowledge with the teacher’s help. Therefore, they could understand the text easier. However, that situation happened because the text was taken from the internet website. Therefore, the texts with the same topic probably contained lots of advanced vocabulary different from the reading texts in the textbook. In this case, students’ response toward the implementation of interactive reading model was good in terms of vocabulary improvement. Conclusion The aim of this study was to describe the implementation of interactive reading model to teach hortatory exposition text anf the students’ responses when they are taught by using that reading model. Firstly, regarding the implementation of the interactive reading model to teach hortatory exposition texts, the researcher concludes that it was conducted by the teacher in these steps: introducing the title/headline; preparing the students’ structure and linguistic feature; focusing on the students’ pronunciation and word recognition; asking the students to find out unknown words by using context and dictionary; requiring the students to transfer the message from the text into a table; asking the students’ opinion and feeling toward the text; and conducting follow-up activities. Secondly, the students’ responses toward the implementation of interactive reading model were good in terms of vocabulary improvement, pronunciation practice, and opportunity for communication. Suggestion Taking into account the results of the study, two suggestions for futher research can be made. First, the teacher should use the text which fulfils the criteria of suitability of content, exploitability, and readability. Second, the next researchers can be concern to use the interactive reading model to teach the different kinds of text and the other levels of the student. REFERENCES Abbott, G., et.al. 1981. The Teaching of English as an International Language. Glasgow: William Collins Sons and Co. Ltd. Anderson, Neil. 2003. Reading. In David Nunan (ed.). Practical English Language Teaching. Singapore: Mc Graw Hill. Ary, Donald. 2010. Introduction to Research in Education 8th Edition. USA: Wadsworth. Berry, James H. 2005. Levels of Reading Comprehension. Retrieved from: www.sc4.com on April 27th. Brown, Douglas H. 2001. Teaching by Principles. An Interactive Approach to Language Pedagogy Second Edition. London: Longman. Correia, Rosane. 2006. Encouraging Critical Reading in the EFL Classroom. English Teaching Forum 44 (1), 16-27. Daniels, Harvey and Steven Zemelman. 2004. Subjects Matter: Every Teacher’s Guide to Content-Area Reading. Portsmouth: Heinemann. De Debat, Elba Villanueva. 2006. Applying Current Approaches to the Teaching of Reading. English Teaching Forum 44 (1), 8-15. Griffiths,G., Sohlberg, M. M., and Biancarosa, G. 2010. A Review of Models of Reading Comprehension with Implications for Adults with mTBI and the Campus Reader. Retrieved from: www.campusreader.org. Harmer, Jeremy. 1998. How to Teach English. Pearson: Longman. Harmer, Jeremy. 2007. The Practice of English Language Teaching fourth edition. Pearson: Longman. Lyutaya, Tatiana. 2011. Reading Logs: Integrating Extensive Reading with Writing Tasks. English Teaching Forum 49 (1), 26-34. Nunan, David. 1998. Language Teaching Methodology. A texbook for teachers. New York: Prentice Hall. Ono, L., Richard Day and Kenton Harsch. 2004. Tips for Reading Extensively. English Teaching Forum 42 (4), 12-18. Papalia. 1987. Interaction of reader and text. In Wilga M Rivers (ed.). Interactive Language Teaching. London: Cambridge University Press. Priyana, Joko. 2008. INTERLANGUAGE: English for Senior High School Students XI Science and Social Study. Jakarta: Pusat Perbukuan, Departemen Pendidikan Nasional. Street, Chris. 2002. Expository Text and Middle School Students: Some Lessons Learned. Voices from the Middle 9 (4), 33-38. Wahjudi, Arjiwati. 2010. Interactive Post-Reading Activities That Work. BAHASA DAN SENI Universitas Negeri Malang Tahun 38 (1),84-92.